PO-33 - Heparin suppresses progression of small cell lung cancer (SCLC) in an orthotopic mouse model. Issue 140 (April 2016) - Taromi, S.; Catusse, J.; Elverfeldt, D.v.; Reichardt, W.; Ledig, B.; Zeiser, R.; Burger, M.
Abstract : Introduction: Lung cancer is the leading cause of cancer-related death worldwide. Small cell lung cancer (SCLC) is thereby a highly aggressive neuroendocrine carcinoma representing about 15% of all lung cancer cases. Due to the highly metastatic behavior and multidrug resistance, the long-term survival of patients is very low. Aim: Current clinical studies revealed an increased survival of SCLC patients treated with heparin. Thus, the role of heparin in SCLC progression was analyzed with the focus on cell adhesion, cell survival and metastasis formation. Materials and Methods: Heparins were tested for their capacities to alter migration, adhesion and viability of SCLC cells in vitro as well as tumor growth and metastasis formation in vivo. Results: Unfractionated heparin (UFH) and low molecular weight heparin (LMWH) both strongly inhibited migration as well as adhesion of SCLC cells to fibronectin and stromal cells. In addition, Heparin induced cellular apoptosis and also increased apoptotic effects of conventional chemotherapeutics in vitro. To investigate the role of LMWH on metastasis formation in vivo, an orthotopic xenograft mouse model with spontaneous metastasis formation has been established. The primary tumors in this mouse model show a marked capacity to metastasize to characteristic distant organs, reflecting advanced steps of malignant progression. Treatment of tumor-bearing mice with LMWH suppressed progression of SCLC. Conclusions: Administration of LMWH in addition to the conventional treatment might reduce metastasis formation and development of chemoresistance, leading to an improved survival rate of patients suffering from SCLC.